The paradox is the intention of the major difference (Journal of the College of Basic Education, 2023)
Paradox is the language of contrast, it is said: the difference of something is a paradox, and a difference, i.e. a clear (1)The linguistic meaning of paradox is limited to the meaning of association, contrast and difference.The term paradox in Arabic is a participle noun (difference) and its root word is (difference).Its source is (differences) and its meaning is the contrast, the abandonment and the distancing, and in this general sense it was notWith the modern problem that the scholars concerned with, but it is an old issue, interest in it began.Since the time of Socrates, Plato and Aristotle, and perhaps before that.The concept of paradox appears in the philosophy of (change), which reaches the point of contradiction.The philosopher Heraclitus, who lived about five centuries before Christ, believed that the truthIt lies only in “expecting the unexpected” (2) as he also believes that “disagreement brings harmonyFrom disagreement comes the entirety of the coalition” (3).Paradox meant, for Aristotle, the evasive use of language.To him, it is a form of rhetoric, and praise is included in the form of slander, and slander in the form of slander.Praise formula (4).The paradox was associated with what he called (was) (the higher structure), and he meant awareness.The subjective (transcendental) which is the “awareness of the existence of a “I am thinking” associated with every experience.. and ofThe path of awareness defines the thinking ego itself as connected, present, and effective over the course of time.A series of his experiences (5) As for the (transcendental) self, it is the “negative self that cannot